1999
DOI: 10.1034/j.1398-9995.1999.00763.x
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of allergy in children due to formaldehyde exposure in homes

Abstract: Low-level exposure to indoor formaldehyde may increase the risk of allergic sensitization to common aeroallergens in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
5
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 16 publications
0
116
5
7
Order By: Relevance
“…These studies, which investigated children's respiratory health in relation to formaldehyde exposures based on stationary indoor measures, have indicated that respiratory impacts can occur at relatively low concentrations, as are found in conventional Australia homes (Garrett et al 1999;Franklin et al 2000). This further supports the need to more directly quantify the actual concentrations of formaldehyde children are being exposed to.…”
Section: Conclusion and Rationale For Studymentioning
confidence: 86%
See 2 more Smart Citations
“…These studies, which investigated children's respiratory health in relation to formaldehyde exposures based on stationary indoor measures, have indicated that respiratory impacts can occur at relatively low concentrations, as are found in conventional Australia homes (Garrett et al 1999;Franklin et al 2000). This further supports the need to more directly quantify the actual concentrations of formaldehyde children are being exposed to.…”
Section: Conclusion and Rationale For Studymentioning
confidence: 86%
“…There has been some limited research undertaken in the field of children's health and formaldehyde, with some useful research undertaken within Australia (Garrett et al 1999;Franklin et al 2000;Rumchev et al 2002). These studies, which investigated children's respiratory health in relation to formaldehyde exposures based on stationary indoor measures, have indicated that respiratory impacts can occur at relatively low concentrations, as are found in conventional Australia homes (Garrett et al 1999;Franklin et al 2000).…”
Section: Conclusion and Rationale For Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient levels of VOCs, including formaldehyde, have been linked to reported asthma in children (Krzyzanowski et al, 1990;Ware et al, 1993;Garrett et al, 1999;Rumchev et al, 2000Rumchev et al, , 2002. The weight of evidence currently available linking VOCs to ill-health in adults suggests that ambient levels found in homes are unlikely to cause adverse effects, but research focusing on the impact of VOCs on the respiratory health of children is sparse.…”
Section: ) Indoor Airmentioning
confidence: 99%
“…The weight of evidence currently available linking VOCs to ill-health in adults suggests that ambient levels found in homes are unlikely to cause adverse effects, but research focusing on the impact of VOCs on the respiratory health of children is sparse. Formaldehyde has been associated with increased prevalence of atopy (Garrett et al, 1999) and higher levels of specific immunoglobulin E (Wantke et al, 1996) in children. Formaldehyde, at levels typically encountered in homes in developed countries, is associated with airway inflammation in both healthy children (Franklin et al, 2000) and adults (Wieslander et al, 1997).…”
Section: ) Indoor Airmentioning
confidence: 99%